Paradoxical leadership and well-being in turbulent times: a time-lagged study - Stynen, Dave; Semeijn, Judith (Frontiers in Psychology, 2023)
Introduction: Paradoxical leadership has recently been put forward as an approach to leadership that may transcend the inherent contradictions in contemporary organizational and personnel management. Empirical research on its potential role for bolstering employee wellbeing remains scarce. This study investigated whether paradoxical leadership positively impacts employee well-being, which is operationalized as employees' job, career and life satisfaction. We rely on Sense-making theory to investigate whether such effects are mediated by the mitigation of employee job insecurity perceptions.Methods: Convenience sampling techniques were used to collect longitudinal survey data between March and September 2021. In total 287 workers provided usable data. Their ages ranged from 18 -67 years and were active in various organizations in the Netherlands.Validated measures were used to assess paradoxical leadership, job insecurity, job, career and life satisfaction. A time-lagged path analysis in Mplus 7.0 was conducted to investigate relationships.The results suggest that paradoxical leadership is positively related to job, career and life satisfaction over time. The relationships between paradoxical leadership and job and career satisfaction are partially mediated by the mitigation of perceived job insecurity.Discussion: Paradoxical leadership plays a role in fostering worker well-being in these turbulent times. Paradoxical leaders may also help their followers to reframe and better deal with challenging working conditions. Despite the longitudinal data design, an additional datawave would allow for more stringent testing of the proposed mediation effect, and due to convenience sampling generalization of findings is limited.